Tuberculosis among indigenous municipalities in Mexico: analysis of case notification and treatment outcomes between 2009 and 2013 - Brenda C. Medel Romero; Martin Castellanos Joya; Martha Angelica Garcia Aviles; Raul Martinez Navarro; Tom Decroo; Rony Zachariah
ABSTRACT Objective To assess trends in 1) tuberculosis (TB) case notification by year and 2) cumulative treatment outcomes (stratified by type of TB) in relation to the proportion of indigenous population in municipalities in a countrywide study in Mexico for the period 2009-2013. Methods This ecological operational research study used municipality data for the five-year study period. As no single identifier variable existed for indigenous persons, municipalities were categorized into one of three groups based on the proportion of their indigenous population (< 25% ("low"), ≥ 25% to < 50% ("medium"), and ≥ 50% ("high")). TB case notification rates (CNRs) were standardized to a 100 000 population. Result For the first four years of the study period (2009 through 2012), for all new TB cases reported nationally, the municipalities with a high proportion of indigenous people (≥ 50%) had the highest CNRs (ranging from 20.8 to 17.7 over that period). In 2013, however, the CNR in the high proportion municipalities dropped to 16.7, lower than the CNR for that year in the municipalities with a medium proportion of indigenous people (P < 0.001). In the municipalities with low and medium proportions of indigenous people, the CNR hovered between 15.1 and 17.3 over the study period. For the 96 195 new TB cases reported over the study period, the treatment success rate ranged between 81% and 84% for all three municipality groups. For previously treated TB cases, CNRs ranged between 1.0 and 1.7 for all three groups over the study period. The average proportion of previously treated TB cases (of all TB cases) was 9% for the three groups in 2009 but dropped to 8% by 2013. The cumulative treatment success rate for all previously treated cases (a total of 8 763 for the study period) was 64% in municipalities with a low proportion of indigenous people, 61% in those with a medium proportion, and 69% in those with a high proportion. Conclusions Despite the slightly higher CNR in municipalities with predominantly indigenous populations, there were no stark differences in TB burden across the three municipality groups. The authors were unable to confirm if the relatively low CNRs found in this study were a reflection of good TB program performance or if TB cases were being missed. A survey of TB prevalence in indigenous people, with individualized data, is needed to inform targeted TB control strategies for this group in Mexico.